Pendekatan Berpikir Sistem dalam Pencegahan Penyimpangan Orientasi Seksual Pada Remaja - Putri Azzahroh; Helmi Helmi; Arni Amir; Adang Bachtiar; Firdawati Firdawati (FORIKES, 2023)
The spread of LGBT groups is currently increasingly unstoppable and increasingly growing attacking Adolescent, where Adolescent are the nation's successor assets. If left unchecked, this crucial problem will trigger social change and trigger the emergence of a hedonic society that is immoral, permissive, and physically and psychologically ill. To fight sexual orientation deviation, a system thinking approach is needed as an effective control strategy, because the influence of system damage caused has an impact on various fields such as health, society, education, and religion. Through system thinking, a strategy is designed that is seen from the input, process, output, and feedback from the sexual orientation prevention system in the form of a sexual orientation prediction model to stem the flow of the massive LGBT movement and spread in Indonesia. The search for the root of the problem in screening adolescent sexual orientation deviations will use iceberg tools and mapped in Causal Loop diagrams. Knowing the root of the problem is an important key in screening, providing education, and therapy so that it suits the needs of each individual. This sexual orientation deviation prevention strategy is expected to be one of the KRR programs and to run effectively, it certainly requires the involvement of various parties, both families, community leaders, religious leaders, educators, health workers, and of course also control from the government as policyholders.Keywords: system thinking; adolescent; lgbt; sexual orientation deviations ABSTRAK Penyebaran kelompok LGBT saat ini semakin tidak terbendung dan semakin berkembang menyerang para remaja, dimana remaja merupakan aset penerus bangsa. Apabila dibiarkan, masalah krusial ini akan memicu perubahan sosial dan munculnya masyarakat hedonis yang amoral, permissif, dan sakit secara fisik maupun psikologis. Sebagai upaya melawan penyimpangan orientasi seksual dibutuhkan pendekatan berpikir sistem sebagai strategi pengendalian yang efektif, karena pengaruh kerusakan sistem yang ditimbulkan berdampak pada berbagai aspek seperti bidang kesehatan, sosial, pendidikan, dan keagamaan. Melalui berpikir sistem dirancang sebuah strategi yang dilihat dari input, proses, output, dan feedback dari sistem pencegahan penyimpangan orientasi seksual yaitu berupa model prediksi orientasi seksual untuk membendung arus massif gerakan dan penyebaran LGBT di Indonesia. Pencarian akar masalah dalam skrining penyimpangan orientasi seksual remaja akan menggunakan alat bantu iceberg tools dan dipetakan dalam Causal Loop Diagram. Diketahuinya akar masalah merupakan kunci penting dalam melakukan skrining, pemberian edukasi, dan terapi sehingga sesuai dengan kebutuhan masing-masing individu. Strategi pencegahan penyimpangan orientasi seksual ini diharapkan dapat menjadi salah satu program KRR dan agar dapat berjalan dengan efektif tentunya diperlukan keterlibatan dari berbagai pihak, baik keluarga, tokoh masyarakat, tokoh agama, tenaga pendidik, tenaga Kesehatan dan pastinya juga kontrol dari pemerintah sebagai pemegang kebijakan.Kata kunci: berpikir sistem; remaja; lgbt; penyimpangan orientasi seksual